ANALISIS REKRUTMEN DAN SELEKSI KARYAWAN (Studi Kasus Pada Karyawan PT. Mitrametal Perkasa) - Estiana, Ria; Nugroho, Edi; Himawan, Himawan (JAB (Jurnal Akuntansi & Bisnis), 2019)
This study aims to determine the magnitude of recruitment and selection factors on employee performance and to find out the most dominant factors affecting employee performance at PT. Mitrametal Perkasa. The research method used is descriptive quantitative with a case study approach. The sample in this study were employees of PT. Mitrametal Perkasa and research data are primary data from the questionnaire. The results of this study indicate that there is a positive correlation between recruitment and selection of prospective employees on employee performance jointly influencing 35%.Â Keywords: recruitment, selection, employee performance